Pemanasan global: Perubahan iklim sebagai dampak meningkatnya emisi gas rumah kaca - Lazuardhi, Alex Febryan (Maliki Interdisciplinary Journal, 2024)
The issue of global warming has been widely discussed, because this has been considered a threat to the security of every living thing, starting from humans, animals, plants or even attacking the ecosystem where these living things live. Global warming occurs because of the increasing amount of greenhouse gas (GHG) emissions produced by the earth. Greenhouse gas emissions are the process of releasing greenhouse gases into the atmosphere over an indeterminate period of time. The largest contributor to greenhouse gas emissions is human activity that continuously uses fossil fuels such as coal, natural gas and oil. Not only that, greenhouse gas emissions also come from industrial sector activities. This global warming causes one of the major threats, one of which is climate change. This climate change poses many major risks, ranging from the disruption of human activities to the threat of animal habitats. To prevent this from continuing, it is important to reduce the production of these emission gases, for example by reducing human activities and industrial activities that produce emission gases and also by utilizing technology derived from renewable energy.